Continuous therapy in standard- and high-risk newly-diagnosed multiple myeloma: A pooled analysis of 2 phase III trials. (December 2018) - D'Agostino, Mattia; De Paoli, Lorenzo; Conticello, Concetta; Offidani, Massimo; Ria, Roberto; Petrucci, Maria Teresa; Spada, Stefano; Marcatti, Magda; Catalano, Lucio; Gilestro, Milena; Guglielmelli, Tommasina; Baldini, Luca; et al.
Abstract: Background: Risk-adapted therapy is a common strategy in curable hematologic malignancies: standard-risk patients receive less intensive treatment, whereas high-risk patients require a more intensive approach. This model cannot be applied in multiple myeloma (MM), which is still incurable. Continuous treatment (CT) is a key strategy for MM treatment, since it improves duration of remission. However, the role of CT according to standard- or high-risk baseline prognosis remains an open question. Patients and methods: We performed a pooled analysis of 2 phase III trials (GIMEMA-MM-03-05 and RV-MM-PI-209) that randomized patients to CT vs fixed-duration therapy (FDT). Results: In the overall patient population (n = 550), CT improved progression-free survival1 (PFS1) (HR 0.54), PFS2 (HR 0.61) and overall survival (OS) (HR 0.71) vs FDT. CT improved PFS1 both in R-ISS I (HR 0.49) and R-ISS II/III patients (HR 0.55). Four-year PFS1 was 38% in R-ISS II/III patients receiving CT and 25% in R-ISS I patients receiving FDT, with similar trends for PFS2 and OS. High-risk patients benefited more from proteasome-inhibitor plus immunomodulatory-based CT than immunomodulatory alone. Conclusion: Good prognosis patients receiving FDT lose their prognostic advantage over high-risk patients receiving CT and high-risk patients may benefit from more intensive maintenance including proteasome inhibitors and immunomodulators.